Incidence and risk factors of Vancomycin-induced thrombocytopenia: a six-year real-world study - Yuanchao Zhu; Lishuang Huang; Jingjing Zhang; Liang Liang; Pengfei Jin (BMC Infectious Diseases)
Abstract Objectives Drug-induced thrombocytopenia has been reported for numerous drugs. Vancomycin-induced thrombocytopenia (VIT) is infrequently and often under-recognized. VIT can lead to the serious consequences of some life-threatening bleeding, especially in high-risk population. However, few studies have focused on VIT. This study aimed to describe the occurrence and manifestation of VIT and evaluate its risk factors in real-world settings. Methods A retrospective case-control study of patients treated with intravenous vancomycin was conducted between January 2018 and December 2023. Results Among the 1269 identified patients, the incidence of thrombocytopenia was 3.3% (42/1269) after a medium of 9 days (range, 2 to 22) of the initiation of vancomycin therapy. Twenty-four patients experienced platelet recovery, and all recovered after discontinuing vancomycin, with a mean duration of 9 days (range, 1 to 35) after vancomycin cessation. The severity of thrombocytopenia varied among these patients, with 45.2% (19/42) experiencing Grade 3 to Grade 4 thrombocytopenia. Multivariate analysis indicated that risk factors for VIT were qSOFA score ≥ 2, underlying renal diseases, duration of vancomycin therapy ≥ 8 days, PLT ≤ 150 × 109/L, and BUN ≥ 12 mmol/L. In the retrospective cohort, among patients with 0–5 risk factors, the incidence rates of VIT were 0.2% (1/556), 1.6% (7/439), 5.8% (10/173), 14.9% (11/74), 42.1% (8/19), and 62.5% (5/8) respectively. Conclusion It is crucial for medical staff to remain vigilant and carefully observe any signs of potential bleeding throughout vancomycin therapy, especially in those with more than 3 combined risk factors.